2022
DOI: 10.3390/met12101733
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Residual Stress Field and Improvement of Fatigue Properties of Thin-Walled Pipes by Filling Laser Shock Peening

Abstract: In the present work, a filling and laser shock peening (LSP) method is put forward and applied to a thin-walled pipe. Specimens were experimentally and numerically investigated to identify the residual stress field and fatigue properties of a pipe with and without LSP treatment. The numerical simulation indicated that the residual compressive stress first increased and subsequently dropped as the laser power density increased, and the extent of influence of the stretching wave, reflected from the lower surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The greater the roughness, the more significant the decrease in the fatigue life is [11]. Many experts in this field have also confirmed that laser shock peening improves the fatigue limit of various different materials [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The greater the roughness, the more significant the decrease in the fatigue life is [11]. Many experts in this field have also confirmed that laser shock peening improves the fatigue limit of various different materials [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%